ABOUT PRODUCTION-TRANSPORT PROBLEM REDUCTION TO THE TWO-LEVEL PROBLEM OF DISCRETE OPTIMIZATION AND ITS APPLICATION - E. Ivokhin; V. Navrodskiy; D. Apanasenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)

(untitled)
In this study, the application of the production and transport task is considered to solve the problem of the distribution of the limited capacities of data transmission channels between different nodes of the computer network. A scheme is proposed for reducing the problem to a two-level continuous-discrete optimization problem. The model is formulated and numerical results are obtained to solve the problem of power distribution in the network of the information and computing center.